NILAI-NILAI ISLAM WASATHIYAH PADA TEMA ISLAM NUSANTARA DALAM BUKU TEKS SKI TINGKAT MTS - Saleh, Fauzi Ansori; Arif, Mahmud (Ta'allum: Jurnal Pendidikan Islam, 2021)
Abstract: These research aims to identify and explain Wasathiyah Islamic Values ​​(NISWA) on the theme of Nusantara Islam in the MTS Level SKI Student Book published by the Ministry of Religion of the Republic of Indonesia in 2015 and 2020 as well as to explain the similarities and differences along with the factors that cause them. As a library research, the data collection technique of this research is through documentation with content analysis techniques in analyzing the data. The results showed that there was NISWA in the two Student Books. This study also shows that there are similarities in the context of NISWA development which include the quantity and type of NISWA, one-to-one correspondence with several NISWA, the spirit of dynamics and creativity through the development of NISWA, the use of a consistent cultural approach and the selection of figures in the learning materials. The difference is seen in the total quantity of NISWA and the focus of its development in each chapter. The factors that cause differences in the development of NISWA in the two Student Books are the direction of the basic paradigm, reference sources and the distinction of Islam Nusantara in the form of material about Islamic boarding schools which is only found in the 2020 Student Book Published.